Distinguishing subaerial and submarine calving with underwater noise - Oskar Glowacki (Journal of Glaciology, 2022)
Iceberg calving is one of the major mechanisms of ice loss from tidewater glaciers and ice sheets, but obtaining accurate estimates of ice discharge that are both continuous and accurate is a challenging task. Recent results have demonstrated the effective application of passive cryoacoustics – the use of naturally generated sounds to study the cryosphere – to quantify subaerial calving fluxes. However, little is known about the acoustic signatures of submarine calving. This study investigates the underwater noise from 656 subaerial and 162 submarine calving events observed at Hansbreen, Svalbard in the summers of 2016 and 2017. Statistical analysis of the acoustic signal shows that the normalized power of the calving noise is log-normally distributed regardless of the calving mode. However, submarine events can be distinguished from subaerial events by using the shape parameter of the log-normal distribution paired with the calving signal duration. The newly developed classification model may potentially be used for two purposes: (1) to study potential causal relationships between these two calving modes and (2) to separate calving fluxes into subaerial and submarine components. The latter will also require knowledge of the relationship between ice mass and sound spectral level for submarine calving events.